Altitude Modulates Concussion Incidence: Implications for Optimizing Brain Compliance to Prevent Brain Injury in Athletes. Issue 6 (8th November 2013) - Smith, David W.; Myer, Gregory D.; Currie, Dustin W.; Comstock, R. Dawn; Clark, Joseph F.; Bailes, Julian E.
Background: Recent research indicates that the volume and/or pressure of intracranial fluid, a physiology affected by one's altitude (ie, elevation above sea level), may be associated with the likelihood and/or severity of a concussion. The objective was to employ an epidemiological field investigation to evaluate the relationship between altitude and concussion rate in high school sports. Hypothesis: Because of the physiologies that occur during acclimatization, including a decline in intracranial compliance (a "tighter fit"), increased altitude may be related to a reduction in concussion rates in high school athletes. Study Design: Cohort study; Level of evidence, 3. Methods: Data on concussions and athlete exposures (AEs) between 2005-2006 and 2011-2012 were obtained from a large national sample of high schools (National High School Sports-Related Injury Surveillance System [High School RIO]) and were used to calculate total, competition, and practice concussion rates for aggregated sports and for football only. Results: Altitude of participating schools ranged from 7 to 6903 ft (median, 600 ft), and a total of 5936 concussions occurred in 20, 618, 915 exposures (2.88 per 10, 000 AEs). When concussion rates were dichotomized by altitude using the median, elevated altitude was associated with a reduction in concussion rates overall (rate ratio [RR], 1.31; P < .001), in competition (RR, 1.31; P < .001), and in practice (RR, 1.29; P < .001). Specifically, high school sports played at higher altitude demonstrated a 31% reduction (95% confidence interval [CI], 25%-38%) in the incidence of total reported concussions. Likewise, concussion rates at increased altitude were reduced 30% for overall exposures, 27% for competition exposures, and 28% for practice exposures in football players ( P < .001). Conclusion: The results of this epidemiological investigation indicate increased physiological responses to altitude may be associated with a reduction in sports-related concussion rates, especially in collision sports. Future research that focuses on the potential prophylactic effect of optimizing outflow impedance and thus reduction of intracranial compliance (a "tighter fit") in humans is warranted to determine the most effective approaches to mitigate sport-related concussion, especially in football players.